Effect of a radical exposure nitridation surface on the charge stability of shallow nitrogen-vacancy centers in diamond. (6th April 2017) - Kageura, Taisuke; Kato, Kanami; Yamano, Hayate; Suaebah, Evi; Kajiya, Miki; Kawai, Sora; Inaba, Masafumi; Tanii, Takashi; Haruyama, Moriyoshi; Yamada, Keisuke; Onoda, Shinobu; Kada, Wataru; et al.
Abstract: A nitridation process of a diamond surface with nitrogen radical exposure far from the radio-frequency plasma for the stabilization of a negatively charged nitrogen-vacancy (NV − ) centers near the surface is presented. At a nitrogen coverage of as high as 0.9 monolayers, high average Rabi contrasts of 0.40 ± 0.06 and 0.46 ± 0.03 have been obtained for single NV − centers formed by shallow nitrogen implantation with acceleration voltages of 1 and 2 keV, respectively. This indicates that nitrogen termination by a radical exposure process produces an electric charge state suitable for single NV − centers near the surface compared with the states obtained for alternatively terminated surfaces.